Japan's economic planning and mobilization in wartime, 1930s-1940s the competence of the state - Miwa, Yoshiro 1948- (New York, N.Y. Cambridge University Press, 2015)
"Although most economists maintain a mistrust of a government's goals when it intervenes in an economy, many continue to trust its actual ability. They retain, in other words, a faith in state competence. For this faith, they adduce no evidence. Sharing little skepticism about the government's ability, they continue to expect the best of governmental intervention. To study government competence in World War II Japan offers an intriguing laboratory. In this book, Yoshiro Miwa shows that the Japanese government did not conduct requisite planning for the war by any means. It made its choices on an ad hoc basis and the war itself quickly became a dead end. That the government planned for the war incompetently casts doubts on the accounts of Japanese government leadership more generally"
Includes bibliographical references (pages 443-452) and index.
Keywords: Japan. -- Kaigun. -- Kokutai -- History -- 20th century; World War, 1939-1945 -- Economic aspects -- Japan; Sino-Japanese War, 1937-1945 -- Economic aspects -- Japan; Industrial mobilization -- History -- 20th century. -- Japan; Military planning -- History -- 20th century. -- Japan; Japan -- Armed Forces -- Mobilization -- History -- 20th century; Japan -- Economic policy -- 1918-1945.; Japan -- Military policy